Sosialisasi Penyakit Skabies : Upaya Pencegahan dan Pengobatannya di Pondok Pesantren Mambaul Ulum Banjarejo Pagelaran Malang - Mulis, Mulis (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The aim of Community Service is to provide health outreach regarding the prevention and treatment of scabies, which is carried out at the Mambaul Ulum Banjarejo Islamic Boarding School, Pagelaran, Malang. This location was determined as a service partner because at the Islamic boarding school most of the students, even the majority of them, had experienced scabies and they did not understand the symptoms, and prevention and treatment efforts when infected by the disease. There are several stages carried out in this service, namely the preparation stage, implementation stage and reflection or evaluation of activities. The result of this service activity is that this socialization brings positive benefits for students because after participating in this socialization activity they know about the symptoms, efforts to prevent and treat scabies. This conclusion was obtained from survey data given to partners after participating in the activity where the data showed that 98 % of partners admit their interest in outreach activities and provide information that is very relevant and useful for them so that they can know the symptoms of scabies and try to prevent or treat it.